1988
DOI: 10.1099/00221287-134-6-1623
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hormones on Trichomonas vaginalis

Abstract: ~~ ~ ~The hormonal milieu can alter susceptibility to infection. The effect of hormones on Trichomonas vaginalis was studied utilizing axenically cultured clinical isolates. Oestrogens, in physiological concentrations, decreased the growth of the organisms and their attachment to mammalian cells in vitro, and acted as a chemorepellent. The specificity of these effects was verified by their being blocked with anti-oestrogens, by the dose-and time-dependency of the responses, and by the lack of effect with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Other studies using euthymic and athymic BALB/c mice found that females are more susceptible than males to developing abscesses following subcutaneous injections of T. vaginalis (Landolfo et al 1981;Martinotti et al 1988). Conversely, some in vitro studies have found that estrogen inhibits T. vaginalis growth (Sugarman and Mummaw 1988) and inhibits a virulence factor, cell-detaching factor, which is correlated with disease severity (Garber et al 1991). This may explain why intravaginal estrogen pellets alleviate disease symptoms (Garber et al 1991).…”
Section: Trichomoniasismentioning
confidence: 91%
“…Other studies using euthymic and athymic BALB/c mice found that females are more susceptible than males to developing abscesses following subcutaneous injections of T. vaginalis (Landolfo et al 1981;Martinotti et al 1988). Conversely, some in vitro studies have found that estrogen inhibits T. vaginalis growth (Sugarman and Mummaw 1988) and inhibits a virulence factor, cell-detaching factor, which is correlated with disease severity (Garber et al 1991). This may explain why intravaginal estrogen pellets alleviate disease symptoms (Garber et al 1991).…”
Section: Trichomoniasismentioning
confidence: 91%
“…DL8 nutrient medium is a chemotactic agent (chemoattractant) compared with PBS (15). To assay chemokinesis separately from chemotaxis, the assay was performed eight times with nutrient medium or PBS on both sides of the filter.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report on the effect of hormones on T. vaginalis described a new assay system for the chemotaxis of this organism and noted again how motile they are (15). An attempt was made to better define the chemotaxis of these organisms and to study the effects of antimicrobial agents on this process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using euthymic and athymic BALB/c mice found that females are more susceptible than males at developing abscesses following subcutaneous injections of T. vaginalis [170]. Conversely, some in vitro studies have found that E2 inhibits T. vaginalis growth [171] and both virulence factor and cell-detaching factor, which are correlated with disease severity [172].…”
Section: In Protozoa Infectionsmentioning
confidence: 99%